Glove Gesture Sensor-Based Motion for Deaf and Mute People Equip with Global Positioning System (GPS) - Nur Zuliyana Binti Mohd Rajdi, Nik; Mujahid Ubaidillah Bin Zakaria, Ahmad; Harris Bin Abdul Ghani, Mohamed; ., . (International Journal of Engineering and Technology, 2019)
The numbers of peoples with deaf-mute disability around the worlds is exponentially increased in numbers nowadays. One of the common limitation faced by deaf-mute people is to communicate with the society. Nowadays, the medium communication that used by them is ‘sign language’. However, sign language is very hard to understand and required proper training to master it. With the development of hand-gesture recognition system, a large-scale of multi device or system has been designed and developed rapidly nowadays. Direct use of the hand as input device is an attractive and easy method to develop. Besides, hand-gesture can provide a complementary modality speech for expressing one idea and communicate each other’s. In this project, we propose to produce a low-cost glove-gesture based motion that can convert the hand gesture into the speech that everyone can understand. In addition, Global Positioning System (GPS) tracking will be embedded into the glove for the deaf-mute person safety and monitoring. . This project will use two main components, which are Arduino UNO and Gesture-Sensor. The circuit will be design to detect the motion from the gloves-based sensor as an input and converted into the sound or voices as an output.